Reconstruction of the Binding Power of Judicial Orders in Constitutional Court Decision Number 169 of PUU XXII 2024 as an Instrument for Reforming Constitutional Procedural Law in Indonesia - Rizki Emil Birham; Afdhal Afdhal (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyze and reconstruct the binding force of judicial orders in the practice of the Constitutional Court as an instrument for reforming constitutional procedural law in Indonesia, based on Decision Number 169/PUU-XXII/2024 of the Constitutional Court. This paper analyzes Law Number 24 of 2003 governing the Constitutional Court and its revisions, as well as the Republic of Indonesia's 1945 Constitution, using a normative juridical method using a statutory and conceptual approach, as well as the doctrine and practice of constitutional justice. The results show that normatively, judicial orders have a legitimate basis in the final and binding nature of Court decisions. However, in practice, they still face serious weaknesses related to the lack of explicit regulations, enforcement mechanisms, and sanctions for non-compliance, thus tending to have only moral binding force. Therefore, legal reconstruction is required by strengthening the normative basis, affirming the position of judicial orders as decisions with coercive power, and establishing oversight and sanction mechanisms to increase the effectiveness of the implementation of Court decisions.